Severe skin toxicity with organ damage under the combination of targeted therapy following immunotherapy in metastatic melanoma. Issue 5 (October 2018) - Lamiaux, Marie; Scalbert, Camille; Lepesant, Pauline; Desmedt, Eve; Templier, Carole; Dziwniel, Véronique; Staumont-Sallé, Delphine; Mortier, Laurent
Abstract : Targeted therapy combination (TTC: antiRAF+antiMEK) is known to improve metastatic melanoma survival. Few severe skin toxicities (grade ≥3) are described with first-line TTC (17% for vemurafenib+cobimetinib and none for dabrafenib+trametinib) in a phase III trial. Among our 42 patients treated by TTC between January 2014 and March 2017, 4.8% (2/42) of those treated in the first line presented severe skin rash versus 19% (8/42) of patients treated in the second line after previous immunotherapy. In particular, we observed one case of Stevens–Johnson syndrome and four cases of severe drug reaction with eosinophilia and systemic symptoms syndrome under TTC in patients who had received immunotherapy previously. Thus, previous immunotherapy appears to play an important role in the skin rash onset and severity induced by TTC.